(untitled) (Research, Society and Development, 2022)
Cell theory condenses studies on the origin, composition and functioning of cells. The first contributors to this theory were Matthias Schleiden and Theodor Schwann who, through their studies, concluded that all living beings are made up of cells. The understanding of basic concepts of cell biology is fundamental for the learning of physiology, reproduction, heredity, propagation of diseases and interactions between living beings. Therefore, from elementary school to high school, science subjects cover cytology topics. However, these are treated in a predominantly theoretical way. Practical classes are extremely important for scientific literacy and should be carried out from basic education onwards. However, there is a lack of experiments that allow the visualization of animal cells in living tissue. In view of this, this article proposes a practical class using the worm Panagrellus redivivus in order to elucidate multicellularity as well as the formation of new cells and the living being through embryogenesis. This nematode is easy to obtain and handling is done using low-cost materials, but the learning gain is very high. It is believed that the use of this experimental model not only facilitates the understanding of the proposed topic but also helps and encourages the scientific training of students.